2021
DOI: 10.1080/13691058.2021.1881618
|View full text |Cite
|
Sign up to set email alerts
|

Being dragged into adulthood? Young people’s agency concerning sex, relationships and marriage in Malawi, Mozambique and Zambia

Abstract: This study aimed to explore how young people exercise agency in rural Malawi, Mozambique and Zambia in relation to sex, relationships and marriage, to inform local programmes aiming to prevent teenage pregnancy and child marriage. In each country, focus group discussions with young people and parents, in-depth interviews with young people and a variety of other participants, and a household survey with young people (15-24 years) were conducted. We found that (child) marriage was often a response to teenage pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
8
0
3
Order By: Relevance
“…Our ndings also corroborate with the notion that in various settings, marriage is perceived to be central to women's life, it provides them a way to 'adulthood' and community respect which, in particular in the absence of alternative economic and social opportunities, can contribute to (choosing) early marriage (34)(35)(36).…”
Section: Discussionsupporting
confidence: 85%
“…Our ndings also corroborate with the notion that in various settings, marriage is perceived to be central to women's life, it provides them a way to 'adulthood' and community respect which, in particular in the absence of alternative economic and social opportunities, can contribute to (choosing) early marriage (34)(35)(36).…”
Section: Discussionsupporting
confidence: 85%
“…We found multiple descriptions of nonconsensual experiences, and a concerning lack of consent vocabulary and understandings. We found that MRY do hold agency, but, as with young people in areas of East Africa, 58,67 East and South Asia, 60,62,68 and the Pacific, 64 this was compromised by contextual, structural and social factors. Often, MRY engaged 'subtle' or 'thin' agency, navigating within and around constraints.…”
Section: Discussionmentioning
confidence: 69%
“…Often, MRY engaged 'subtle' or 'thin' agency, navigating within and around constraints. 58,67 Relationships were highly significant to MRY; relationships with family, community, peers and partners could impede and enable rights actualisation. Migration disrupts social networks, heightening the importance of family and community connections in resettlement, or bringing pressure to maintain bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study demonstrated increased intention, the intervention was insufficient to open conversations between adults and adolescents and young people, which may make it less likely that adolescents and young people will access STI testing [63]. Modernization in the timing and content of sexual teachings [64,65] and health programs that increase adolescents' and young peoples' assertiveness can increase SRH communication with parents and other significant adults, with anticipated benefits [63]. In addition, parent-based interventions show a significant association with improved condom use and parent-child sexual communication, especially when focused on young adolescents and targeted at both parents and adolescents [66].…”
Section: Principal Findingsmentioning
confidence: 99%